Strengthening Nigeria’s national home-grown school feeding program in Osun State - Amare, Mulubrhan; Bamiwuye, Temilolu; Idowu, Ifetayo (International Food Policy Research Institute, 2024)
As part of the CGIAR Initiative on Fragility, Conflict and Migration, and CGIAR Initiative on National Policies and Strategies, the International Food Policy Research Institute (IFPRI) recently visited Osun State, Nigeria to explore opportunities for enhancing the National Home-Grown School Feeding Program (NHGSFP).